S. 1440, THE 'NON-SMOKERS RIGHT ACT OF 850000 - CHILCOTE,SD JR (Tufts Archival Research Center, 2007)
Marginalia; Memo from Samuel D Chilcote, Jr to members of the Tobacco Institute Executive Committee. Discusses S. 1440, the "Non Smokers Right Act of 1985." Alerts committee that a revised version was requested and informs them of plans to place "holds" on the legislation in the senate as well as intensify contacts with Congress members.